Developing Pupils’ Learning and Research Skills on the Basis of Physical Experiments - Djabbar Eshkulovich, Usarov; Kusharbay Tashbaevich, Suyarov (International Journal of Psychosocial Rehabilitation, 2020)
This article was written with the aim of developing a methodological system for the development of educational and research skills based on physical experiments in students of the academic lyceum in the direction of exact sciences. Research objectives: studying the development of educational and research skills in students as a pedagogical problem based on the analysis of pedagogical and scientific-methodical literature, developing the theoretical foundations of a methodological system for developing educational and research skills in students and its model; coverage of the pedagogical and psychological conditions of the teacher and student in the process of developing educational and research skills in students and assessing the level of development of educational and research skills in students; development of an optional course program for the development of educational and research skills in students based on physical experiments; development of recommendations on the use of mathematical models and programs and modern educational technologies in the implementation of educational research aimed at the development of educational research skills in students.